Application of professional and safe transport nursing mode in intrahospital transport of critically ill patients (专业安全转运护理模式在急诊危重症患者院内转运中的应用) - LIU Ai (刘爱); TONG Lu (佟璐); ZHAO Zitong (赵紫彤); ZUO Ling (左琳); FENG Ying (冯莹); QUAN Zhiqin (权志琴); MING Yue (明月) (Journal of International Translational Medicine Limited, 2023)
Objective To explore the application value of professional and safe transport nursing mode in intra--hospital transport of critically ill patients. Methods Totally 80 patients who required intrahospital transport were selected as the control group. The adverse events occurred in the intrahospital transport were investigated to find out the potential safety hazards, transport handover form was updated, and training for nurses was carried out. A comprehensive evaluation on patients was conducted before intrahospital transport, relevant instruments and personnel were prepared, and professional and safe transfer nursing mode was adopted for intrahospital transport. Another 80 patients who required intrahospital transport were selected as the study group. The total incidence of adverse events during transport and the time cost in transport were observed and compared between two groups. Results The averaged time of transport in the study group was shorter than that in the control group (P＜0. 05) . The total incidence of adverse events in the study group was lower than that in the control group (P＜0. 01). Conclusion The application of professional and safe transport nursing mode in intrahospital transport of critically ill patients can further reduce the risk of adverse events, shorten the transport time, and improve the transport safety. (目的 探讨专业安全转运护理模式在急诊危重症患者院内转运中的应用效果。方法 选取2021年3月-8月收治的需院内转运患者80例为对照组, 调查急危重症患者转运中不良事件, 找出转运时存在的安全隐患, 重新更新转运交接单, 并对护士进行转运培训; 对转运前患者充分评估, 做好转运前仪器、人员等准备工作, 采用专业安全转运护理模式进行转运。选取 2021年9月-2022年3月收治的需院内转运患者80例为研究组。统计两组患者转运中的不良事件发生率及院内转运时间。结果 研究组的院内转运时间短于对照组, 差异有统计学意义(P＜0. 01)。 研究组不良事件总发生率低于对照组, 差异有统计学意义(P＜0. 05)。结论 在急危重症患者转运过程中运用专业安全转运护理模式, 能够进一步降低不良事件发生的风险, 缩短转运时间, 从而提高转运安全。)